Lactobacilli Isolated From Wild Boar (Sus scrofa) Antagonize Mycobacterium bovis Bacille Calmette-Guerin (BCG) in a Species-Dependent Manner - Bravo, Maria; Combes, Theo; Martinez, Fernando O; Cerrato, Rosario; Rey, Joaquín; Garcia-Jimenez, Waldo; Fernandez-Llario, Pedro; Risco, David; Gutierrez-Merino, Jorge (Frontiers in Microbiology, 2019)
Background: Wildlife poses a significant burden for the complete eradication of bovine tuberculosis (bTB). In particular, wild boar (Sus scrofa) is one of the most important reservoirs of Mycobacterium bovis, the causal agent of bTB. Wild boar can display from mild TB lesions, usually found in head lymph nodes, to generalized TB lesions distributed in different anatomical regions; but rarely clinical signs, which complicates the diagnosis of M. bovis infection and bTB control. Among the possibilities for this variability in lesion distribution is the influence of the host-beneficial commensal-primed immune barrier. In this respect, beneficial microbes may delay bTB dissemination as a consequence of an antagonistic competition for nutrients and phagocytes. In order to explore this possibility, we have tested whether typical commensals such as lactobacilli have the capacity to reduce the survival rate of the surrogate M. bovis strain Bacillus Calmette-Guerin (BCG); and to modulate its phagocyte intake. Results: Three Lactobacillus species, L. casei, L. plantarum and L. salivarius, isolated from wild boar feces displayed a pH-dependent inhibitory activity against BCG and influenced its intake by porcine blood phagocytes in a species-dependent manner. All lactobacilli showed a very significant bactericidal effect against BCG at low pH, but only isolates of L. plantarum and L. casei displayed such antimycobacterial activity at neutral pH. The genomes of these isolates revealed the presence of two-peptide bacteriocins whose precursor genes up-regulate in the presence of BCG cells. Furthermore, L. plantarum reduced significantly the BCG phagocytic intake, whereas L. casei had the opposite effect. L. salivarius had no significant influence on the phagocytic response to BCG. Conclusions: Our in vitro results show that lactobacilli isolated from wild boar antagonize BCG as a consequence of their antimycobacterial activity and a competitive phagocytic response. These findings suggest that commensal bacteria could play a beneficial role in influencing the outcome of bTB dissemination. Further work with lactobacilli as a potential competitive pressure to control bTB will need to take into account the complex nature of the commensal microbiome, the specific immunity of the wild boar and the in vivo infection context with pathogenic strains of M. bovis.